The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/ptr.4906
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of 10 Guadeloupean Plants

Abstract: Screening of the antifungal activities of ten Guadeloupean plants was undertaken to find new extracts and formulations against superficial mycoses such as onychomycosis, athlete's foot, Pityriasis versicolor, as well as the deep fungal infection Pneumocystis pneumonia. For the first time, the CMI of these plant extracts [cyclohexane, ethanol and ethanol/water (1:1, v/v)] was determined against five dermatophytes, five Candida species, Scytalidium dimidiatum, a Malassezia sp. strain and Pneumocystis carinii. Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…In the case of Pisonia acuelata, antifungal activity against several fungi had been evaluated, but only activity against Pneumocystis carinii was reported. 64 We found that extract of this plant to be active against K. pneumoniae. Finally, the whole plant extract of Urena sinuata showed a moderate activity against S. aureus and a very good activity against K. pneumoniae.…”
Section: Discussionmentioning
confidence: 82%
“…In the case of Pisonia acuelata, antifungal activity against several fungi had been evaluated, but only activity against Pneumocystis carinii was reported. 64 We found that extract of this plant to be active against K. pneumoniae. Finally, the whole plant extract of Urena sinuata showed a moderate activity against S. aureus and a very good activity against K. pneumoniae.…”
Section: Discussionmentioning
confidence: 82%
“…B. simaruba is one of the traditional plants with most scientific evidence in many fields, possess cytotoxicity, and antiviral properties against herpes simplex viruses (HSV-1 and HSV-2) [ 15 ], antifungal activity [ 16 ], antibacterial [ 17 - 19 ], anti-inflammatory [ 20 - 23 ], the present study describes some cardiovascular properties; was the only tested extract that reduced the HR in rats with and without hypertension, the only with negative chronotropic effect in all experimental groups, evoking the effects of the beta blockers [ 24 - 26 ], further experiments must test if this effect is observed or not in models of sympathetic denervation [ 27 ] or in the presence of selective adrenergic antagonist to elucidate the pharmacodynamic mechanism of action. The single oral administration of the extract decreased the BP for more than 40 h; antihypertensive drugs action should last at least 24 h to enhance adherence [ 28 , 29 ], postulating it as a novel long-acting antihypertensive drug.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the differences in the amount of disease present in each forest species may be related to the production of secondary metabolites and the anatomy of their leaves. In Platymisicium species, the presence of flavonoids, isoflavonoids and other compounds with antifungal and cytotoxic properties has been reported (Cardoso-Lopes et al, 2008;Cuellar et al, 2020), although plant metabolites produced by E. cyclocarpum may also have antifungal activity (Pacheco et al, 2012;Biabiany et al, 2013). Arambarri et al (2006) observed the presence of conspicuous epicuticular waxes in Enterolobium spp., a common feature of species adapted to dry environments, which can confer resistance to penetrating pathogens.…”
Section: Incidence and Severity Of Foliar Anthracnose And Their Relationship With Tree Defoliationmentioning
confidence: 99%